METODE KONTEKSTUAL (CONTEXTUAL TEACHING AND LEARNING) DALAM PEMBELAJARAN TATA BAHASA JEPANG DASAR (SHOKYOU BUNPO) BAGI MAHASISWA SEMESTER II SASTRA JEPANG SEKOLAH TINGGI BAHASA ASING SARASWATI DENPASAR - Dewa Putu Adnyana (SPHOTA: Jurnal Linguistik dan Sastra, 2015)
ABSTRACT This research is a class action research applying the Contextual Teaching and Learning. The purpose of applying the method is to increase the student ability in basic Japanese grammar (Shokou Bunpo). The research shows that the average score of the students ability in basic Japanese grammar (Shokyou Bunpo) before the application of the Contextual Teaching and Learning was 51 which is categoriced as low. The ability of the students after having the method in the first cycle was 69, and then increased into 80 after the scond cycle. As a whole, the students could reach the score of 80 after second cycle which is categorized as good. Thus the increase of their scores was ranging from low in the first test, into sufficient in the second test, and finally good in the third test. Make simple grammatical Japanese sentences. At this stage the student could make simple grammatical Japanese sentences. The factors affecting the success of the method were the interest and the motivation of the student, good group work, braveness, the habits of the students, their speaking skills, adequate facilities, and the campus environment. As the conclusion, it can be stated that the application of the method of Contextual Teaching and Learning can improve the student basic Japanese grammar (Shokyou Bunpo). Key words: CTL method, improvement, basic Japanese grammar, student’s ability.